Spontaneous Remission After a Hypercalcemic Crisis Caused by an Intracystic Hemorrhage of Bilateral Parathyroid Adenomas: A Case Report and Literature Review - Liu, Yaoxia; Li, Jianwei; Liu, Hui; Yang, Han; Qiao, Jingtao; Wei, Tao; Wang, Tao; Yu, Yerong (Frontiers in Endocrinology, 2021)
Background Hyperparathyroidism is a common cause of hypercalcemia; however, spontaneous remission after a hypercalcemic crisis caused by an intracystic hemorrhage of parathyroid adenomas is very rare. The question, then, is “What is the best treatment strategy for this type of case?” Method A 47-year-old male patient with primary hyperparathyroidism and a hypercalcemic crisis is reported. Hypercalcemia was spontaneously relieved thereafter. Postoperative paraffin pathology results indicated an intracystic hemorrhage of bilateral parathyroid adenomas. Results After the case report, a literature review is also included to summarize the clinical features of this patient and to provide special reference for clinical diagnosis and treatment of similar cases. Conclusions The choice of surgical timing for such cases can be made based on the comprehensive consideration of clinical symptoms and changes in parathyroid function.